Noncanonical mono(ADP-ribosyl)ation of zinc finger SZF proteins counteracts ubiquitination for protein homeostasis in plant immunity - Kong, L; Feng, B; Yan, Y; Zhang, C; Kim, JH; Xu, L; Rack, JGM; Wang, Y; Jang, J-C; Ahel, I; Shan, L; He, P (Cell Press, 2021)
Protein ADP-ribosylation is a reversible post-translational modification that transfers ADP-ribose from NAD+ onto acceptor proteins. Poly(ADP-ribosyl)ation (PARylation), catalyzed by poly(ADP-ribose) polymerases (PARPs) and poly(ADP-ribose) glycohydrolases (PARGs), which remove the modification, regulates diverse cellular processes. However, the chemistry and physiological functions of mono(ADP-ribosyl)ation (MARylation) remain elusive. Here, we report that Arabidopsis zinc finger proteins SZF1 and SZF2, key regulators of immune gene expression, are MARylated by the noncanonical ADP-ribosyltransferase SRO2. Immune elicitation promotes MARylation of SZF1/SZF2 via dissociation from PARG1, which has an unconventional activity in hydrolyzing both poly(ADP-ribose) and mono(ADP-ribose) from acceptor proteins. MARylation antagonizes polyubiquitination of SZF1 mediated by the SH3 domain-containing proteins SH3P1/SH3P2, thereby stabilizing SZF1 proteins. Our study uncovers a noncanonical ADP-ribosyltransferase mediating MARylation of immune regulators and underpins the molecular mechanism of maintaining protein homeostasis by the counter-regulation of ADP-ribosylation and polyubiquitination to ensure proper immune responses.